2017
DOI: 10.4183/aeb.2017.195
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Ovarian Stimulation in Endometriosis Patients Can Be Individualized by Anti-Mullerian Hormone Levels

Abstract: Context. Anti-Mullerian hormone (AMH) assay is becoming the best indicator of successful IVF treatment response to fertility drugs and could be a useful marker of embryo implantation potential. Various protocols are being used for controlled ovarian stimulation (COS), but there is an uncertainty regarding the implementation of the best protocol for endometriosis patients and also little evidence is available concerning the clinical value of AMH levels in endometriosis.Objective. This study aimed to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 43 publications
3
20
0
Order By: Relevance
“…[13][14][15][16][17][18][19][20] In these studies, 1721 cycles used the long GnRHagonist protocol and 1040 cycles used the GnRHantagonist protocol. Six retrospective analyses, [13][14][15][16][17]20 one cross-sectional study 18 and one RCT 19 were identified. Each study was undertaken at a single centre, and all inclusion/exclusion criteria were available.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…[13][14][15][16][17][18][19][20] In these studies, 1721 cycles used the long GnRHagonist protocol and 1040 cycles used the GnRHantagonist protocol. Six retrospective analyses, [13][14][15][16][17]20 one cross-sectional study 18 and one RCT 19 were identified. Each study was undertaken at a single centre, and all inclusion/exclusion criteria were available.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…For the long GnRH-agonist protocol, four studies administered triptorelin, 14,15,18,19 two studies administered leuprorelin 16,17 and one study administered decapeptyl 13 daily starting from day 20 to 21 of the previous menstrual cycle. One study 20 did not specify which GnRH agonist was used and started treatment after day 21 of the preceding cycle.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…AntiMullerian hormone (AMH) levels have a significant accuracy in pregnancy prediction in patients with ovarian endometriosis [12]. The role of neurotrophins in eutopic endometrium from endometriosis-patients was investigated and no differences were found between patients with and without endometriosis with regards to the neurite outgrowth of sensory ganglia [13]. Pelvic nerve-sparing surgery is effective in improving intestinal symptoms after performing radical surgery for endometriosis which needed segmental intestinal resection [14].…”
Section: F O R P U B L I C a T I O Nmentioning
confidence: 99%
“…Infertility in endometriosis has multiple mechanisms, including the production of inflammatory mediators with damage to oocytes and sperm, reducing anti-müllerian hormone with an impact on follicular reserve, underlying adhesions, ovarian cysts and changes in tubal anatomy (7). This disorder affects women's health and quality of life, with consequences for personal, romantic, family and workplace relationships (8).…”
Section: Introductionmentioning
confidence: 99%